Effects of dietary organic acids on the growth and feed efficiency of Pacific white shrimp, Litopenaeus vannamei - Jamis, Jhumar O.
The interest in seeking antibiotic alternative substances that could inhibit pathogens and also act as alternative growth promoters (AGP) has arisen due to greater restrictions or ban of commercial antibiotics. Organic acids and their salts had received an increasing global attention as AGPs and prophylactic against bacterial pathogens. One of the cheap sources of organic acids are vinegar. In this study, two separate 60-day feeding experiments and one attractability test were conducted. The first feeding experiment (experiment 1) evaluated the growth performance, feed efficiency, and survival of Litopenaeus vannamei fed with diet supplemented with 2% distilled water (control), apple cider vinegar (ACV), coconut sap vinegar (CSV), cane vinegar (CaV) and sodium acetate (NaOAc) salt. Attractability of experiment 1 diets were assessed using multiple-chambered rectangular tanks. The result showed that shrimp fed with organic vinegar supplemented diets showed as significantly higher weight gain, SGR and significantly lower FCR, with CSV determined as the best AGP (p<0.05). Attractability test further confirmed that CSV diet was significantly more attractive than the other diets (p<0.05). The second feeding experiment (experiment 2) assessed the efficiency of CSV at different concentrations (0%, 2%, 4%, 6%, and 8%). The result of experiment 2 showed that at 2% and 4% CSV supplementation, shrimp exhibited significantly higher (p<0.05) growth performance.